Klasyfikacja gmin miejsko-wiejskich województwa mazowieckiego według poziomu rozwoju - Wojewódzka, Agnieszka (The Mazowieckie Voivodship Rural-Urban Local Communites Classification According to the Level of Their Development, 2007)
The aim of the article is to compare the Mazowieckie voivodship urban-rural local governments in terms of their socio-economic development level. There were mentioned some methods of measure local development, which are used in a theory. The author took under the consideration three criteria, namely the contact-related, the formal, and statistical one. They were used to choose a group of the variables, describing the research phenomenon. Based on the Regional Data Bank (prepared by the Central Census Bureau) synthetic indexes for all rural-urban the Mazowieckie voivodship were formed. The indexes allowed to compare the developed potential selected communities in a particular period (2004). In the next step, taking into account the indexes, the local communities were sorted into a growing order. It is significant, that the internal diversity in terms of development level is a feature of the Mazowieckie voivodship. The leaders among rural-urban local governments come from Warszawski subregion and they are in the vicinity of Warsaw.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 361-369